The smut fungi of Greenland - Cvetomir M. Denchev (Pensoft Publishers, 2020)
The first taxonomic treatment of the smut fungi in Greenland is provided. A total of 43 species in 11 genera are treated and illustrated by photographs of sori, microphotographs of spores in LM and SEM, and distribution maps. Two species, Anthracoidea pseudofoetidae and Urocystis tothii, are recorded as new from North America. Thirteen species, Anthracoidea altera, A. capillaris, A. limosa, A. liroi, A. pseudofoetidae, A. scirpoideae, A. turfosa, Microbotryum lagerheimii, M. stellariae, Schizonella elynae, Stegocintractia luzulae, Urocystis fischeri, and U. tothii, are reported for the first time from Greenland. The most numerous distribution groups are the following: circumpolar-alpine and Arctic-alpine species - 14; circumboreal-polar species - 10; and circumpolar and Arctic species - 6. The most widely distributed smut fungi in Greenland are Anthracoidea bigelowii, A. elynae, Microbotryum bistortarum, and M. vinosum. Most species were found in the High Arctic zone (29 species), while from the Low Arctic zone and the Subarctic zone, 26 and 19 species were known, respectively. Ten species, Anthracoidea bigelowii, A. capillaris, A. elynae, Microbotryum bistortarum, M. koenigiae, M. pustulatum, M. silenes-acaulis, M. vinosum, Schizonella elynae, and Urocystis sorosporioides, were recorded from all three zones. Only plants belonging to six families, Cyperaceae, Poaceae, Juncaceae, Ranunculaceae, Caryophyllaceae, and Polygonaceae, out of a total of 55 in the flora of Greenland, hosted smut fungi. Carex was the genus with the highest number of host species (22). The total number of the host plants (45 species) was 8.5 % out of a total of 532 vascular plants in the flora of Greenland.